Influence Work-Family Conflict, Family-Work Conflict on The Performance of Women Nurses Moderated By Job Satisfaction In Yogyakarta Grhasia Mental Hospital - Anang Setiawan; Winarno Winarno; Sri Dwi Ari Ambarwati (AIBPM Publisher, 2024)
ABSTRACT This study aims to determine the effect of work-family conflict, a family-work conflict on performance with job satisfaction as a mediation of female nurses at the Grhasia Mental Hospital, Yogyakarta. This study uses a descriptive quantitative approach, the population in the survey is all female nurses as many as 92 nurses. For the sample used, namely female nurses with civil servant status as many as 84 nurses, with a research sampling technique using purposive sampling. The data used are primary data obtained through questionnaires and interviews. The analytical method used in this study is Structural Equation Model (SEM) with partial Least Square (PLS) 4.0. The results of this study indicate that work-family conflict negative and significant effect on the performance of female nurses, family-work conflict negative and significant influence on female nurses, work-family conflict negative effect on the performance of female nurses at Grhasia Yogyakarta Hospital moderated by job satisfaction, the family-work conflict did not affect the performance of female nurses at Grhasia Yogyakarta Hospital moderated by job satisfaction.